The accuracy of a diagnosis of pneumonia in the emergency department - Alaa Atamna; Shachaf Shiber; Muhammad Yassin; Michael J. Drescher; Jihad Bishara (International Journal of Infectious Diseases, 2019)
Background: Achieving a high degree of diagnostic accuracy of infections in the emergency department (ED) is crucial since a delay in diagnosis can lead to increased mortality, whereas overdiagnosis can lead to antibiotic overprescription. Limited data are available as to ED diagnostic accuracy of infections. The aim of this study was to demonstrate the degree of discordance of an ED diagnosis of pneumonia in relation to an internal medicine ward’s discharge diagnosis of hospitalized adults. Methods: We reviewed the records of all adults hospitalized in internal wards from November 2017-January 2018 diagnosed with an acute infection by an ED physician. The primary outcome was the discordance degree of an ED pneumonia diagnosis compared to the internal ward discharge diagnosis. The influence comorbidities and clinical characteristics on the diagnostic discordance were also evaluated. Results: The study included 875 adults; 434 were admitted with an ED diagnosis of a specific infection. Pneumonia was the most frequent ED diagnosis (n = 195, 45%), of them, 56 (29%) were discordant diagnosis in the internal ward. Conclusion: Interpretation of chest X-rays with the assistance of a radiologist might help in reducing overdiagnosis and minimize antibiotic overprescription, thus improving the ED diagnostic accuracy of pneumonia. Keywords: Infection, Pneumonia, Emergency department, Diagnosis, Accuracy